Monitoring Benthic classification: a comparative study of pixel-based and object-based using satellite imagery / Dr. Ainon Nisa Othman and Nur Hanisah Hashim - Othman, Ainon Nisa; Hashim, Nur Hanisah (College of Built Environment, 2023)
Coral reef is one of the most complex marine environmental system, biodiverse, and productive ecosystem on the planet, which play important role for millions of people in major social, economic, and cultural especially for future generation.